Penerapan Penilaian Pembelajaran Kurikulum 2013 Dalam Meningkatkan Partisipasi Aktif Siswa Siswa Di Sekolah Dasar - Ai Nurul Nurohmah; Chendi Maulana Baharudin Yusuf; Jenisa Tasya; Prihantini Prihantini (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Learning assessment is an important part of the learning process. Appropriate assessment can provide accurate information about student competency achievement. The 2013 curriculum (K-13) learning assessment emphasizes authentic assessment, namely assessment that reflects actual learning. Authentic assessment can increase students' active participation in learning. This research aims to determine the inhibiting and supporting factors for implementing the 2013 curriculum learning assessment in increasing students' active participation. The research uses descriptive qualitative methods using a literature study approach. Based on the research results, the implementation of the 2013 curriculum learning assessment in increasing students' active participation can be carried out well. This is proven by the existence of assessment variables based on indicators for assessing attitudinal competence, knowledge competence and skill competence that students have fulfilled. Apart from that, the implementation of learning assessment in the 2013 curriculum is considered quite influential in increasing students' active participation because it can be seen in students' attitudes, knowledge and skills when receiving or implementing the learning material provided.